Reader, I murdered him (HarperCollins, Clarion Books, an imprint of HarperCollinsPublishers, Blackstone Publishing, 2023)
"Attending boarding school in London, Adele enters the glittering world of society girls and their wealthy suitors, until a violent assault leads her to a roguish young con woman, and together, they become vigilantes who mete out justice."--

Riley Park (Orca Soundings, ,, 2009)
The victim of a vicious assault, seventeen-year-old Corbin struggles to get his life back and deal with the loss of his best friend.

Not your idol: Vol. 1 (Not your idol, 1,, 2020)
"In the wake of an assault, Nina Kamiyama, a former idol in the group Pure Club, shuns her femininity and starts dressing as a boy. At high school, she keeps to herself, but fellow student Hikaru Horiuchi realizes who she is. What secrets is she keeping? The shocking drama starts"--Back cover.

Not your idol: Vol. 2 (Not your idol, 2,, 2020)
"Heartbroken Nina Kamiyama is a former idol. She's decided to keep her past identity a secret for her personal safety, but the dangerous situation intensifies when another discovers who she really is. Who can she trust?"--Page [4] of cover.